(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
в данной статье раскрывается понятие правового нигилизма и его признаки, специфика которых анализируется теоретически и практически. Также были проанализированы мнения ученых-теоретиков, опытных практиков в этой области. this article covers the concept of legal nihilism and their signs, the specifics of which are analyzed theoretically and practically. Also, the opinions and opinions of theoretical scientists, experienced practitioners of this field were analyzed.